EVALUATION OF READING PARK MANAGEMENT BASED ON THE CIPP MODEL IN INCREASING CHILDREN'S INTEREST IN READING - Syarifudin Yunus; Didik Notosudjono; Martinus Tukiran (Pedagogic Research-Applied Literacy Journal, 2024)
Reading parks play an important role in increasing children's interest in reading. This study aims to measure the effectiveness of reading park management in Bogor Regency, using the CIPP (Context, Input, Process, Product) model qualitatively. The instruments used include document studies, interviews, questionnaires, observations, and focus group discussions. Data analysis is an interactive analysis that is presented in its entirety. The results of the study describe that the evaluation of the context component is classified as good with a score of 4.03, the input component is sufficient - 3.29, the process component is sufficient - 3.40, and the product component is sufficient - 3.55. It is concluded that the evaluation of the management of reading parks in Bogor Regency is classified as "quite effective", with an average score of 3.56. There are three challenges faced by reading parks, namely 1) minimal government attention, 2) low public awareness, and 3) a small collection of books. The management of reading parks must ensure that there are readers, books, and commitment from the managers. So that reading parks can increase children's interest in reading, in addition to being a catalyst for improving the quality of human resources to boost Indonesia's Human Development Index (HDI).